Prediction and prevention of preeclampsia in women with preexisting diabetes: the role of home blood pressure, physical activity, and aspirin - Do, Nicoline Callesen; Vestgaard, Marianne; Nørgaard, Sidse Kjærhus; Damm, Peter; Mathiesen, Elisabeth R.; Ringholm, Lene (Frontiers in Endocrinology, 2023)
Women with type 1 or type 2 (preexisting) diabetes are four times more likely to develop preeclampsia compared with women without diabetes. Preeclampsia affects 9%–20% of pregnant women with type 1 diabetes and 7%–14% of pregnant women with type 2 diabetes. The aim of this narrative review is to investigate the role of blood pressure (BP) monitoring, physical activity, and prophylactic aspirin to reduce the prevalence of preeclampsia and to improve pregnancy outcome in women with preexisting diabetes. Home BP and office BP in early pregnancy are positively associated with development of preeclampsia, and home BP and office BP are comparable for the prediction of preeclampsia in women with preexisting diabetes. However, home BP is lower than office BP, and the difference is greater with increasing office BP. Daily physical activity is recommended during pregnancy, and limiting sedentary behavior may be beneficial to prevent preeclampsia. White coat hypertension in early pregnancy is not a clinically benign condition but is associated with an elevated risk of developing preeclampsia. This renders the current strategy of leaving white coat hypertension untreated debatable. A beneficial preventive effect of initiating low-dose aspirin (150 mg/day) for all in early pregnancy has not been demonstrated in women with preexisting diabetes.